2015
DOI: 10.1371/journal.pone.0125959
|View full text |Cite
|
Sign up to set email alerts
|

Structural Bases for the Regulation of CO Binding in the Archaeal Protoglobin from Methanosarcina acetivorans

Abstract: Studies of CO ligand binding revealed that two protein states with different ligand affinities exist in the protoglobin from Methanosarcina acetivorans (in MaPgb*, residue Cys(E20)101 was mutated to Ser). The switch between the two states occurs upon the ligation of MaPgb*. In this work, site-directed mutagenesis was used to explore the role of selected amino acids in ligand sensing and stabilization and in affecting the equilibrium between the “more reactive” and “less reactive” conformational states of MaPgb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The kinetics of NO 2 − reduction from Mt -Nb(II), At -Nb(II), Dr -Nb(II), and Hs -Nb(II) (i.e., of Nb(II)-NO formation) were analyzed in the framework of the minimum reaction mechanism depicted in Scheme 1 [ 27 , 29 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…The kinetics of NO 2 − reduction from Mt -Nb(II), At -Nb(II), Dr -Nb(II), and Hs -Nb(II) (i.e., of Nb(II)-NO formation) were analyzed in the framework of the minimum reaction mechanism depicted in Scheme 1 [ 27 , 29 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Following the approach we exploited other Hbs, both pentacoordinated, like human Hb (Sottini, Abbruzzetti, Spyrakis, et al, 2005), protoglobin (Tilleman et al, 2015), and hexa-coordinated, like human Cygb (Gabba et al, 2013), Ngb (Abbruzzetti et al, 2009;Boron, Capece, et al, 2015) plant Hbs (Abbruzzetti et al, 2021(Abbruzzetti et al, , 2007Bisht et al, 2011), and nitrophorins (Abbruzzetti, He, et al, 2012), we used a minimal kinetic model, reported in Scheme 1, to perform a global analysis of V 1 amplitudes at 1 and 0.1 atm CO. The scheme, derived from the MD simulations results, takes into account transient binding at the primary docking site, ligand exchange with the solvent, and migration to an off-pathway temporary docking site (Tr2).…”
Section: Ligand Recombination Kinetic Modelmentioning
confidence: 99%